Model Pembelajaran Kumon Secara Daring Dalam Kemampuan Membaca Bahasa Jerman - Diannisa Pratiwi; Nurming Saleh; Misnawaty Usman (Universitas Negeri Makassar, 2021)
Abstract. The purpose of this study was to obtain data about the effectiveness of online Kumon learning model in reading skill in German in class XI SMA Negeri 8 Makassar. This research was a ‘true experiment’ research. The population of this study were students of class XI SMA Negeri 8 Makassar which consisted of 9 classes of 297 students. The sample technique that used was random sampling. The subject of this research was students of class XI SMA MIPA 6 which consisted by 33 students as the experimental class and students of class XI IPS 1 which consisted by 33 students as the control class. The results of data analysis using t-test was tcount 6.49> ttable 1.999 at α 0.05 level. The results showed that the online Kumon learning model was effective in the reading ability of German students of class XI SMA Negeri 8 Makassar.